PERANCANGAN SISTEM PENGUKURAN KINERJA MANAJEMEN DENGAN KONSEP STRATEGY MAPS DAN BALANCED SCORECARD PADA KANTOR LINGKUNGAN HIDUP DAERAH KABUPATEN NGANJUK - Retika Nirwana Skar Sari (Universitas Islam Kadiri, 2020)
The purpose of this research is to design the strategy maps balanced scorecard concept in the Regional Environmental Office Nganjuk. Concept Strategy Maps is a picture that connects between the factors that exist in an organization's critical succes factors and describe strategies, goals and measurements. While the Balanced Scorecard consists of two words, namely the Balanced (balanced) and the scorecard (scorecard). Results The strategy used in the Office of the Regional Environmental Nganjuk is focused strategies that focus on the specific purpose of serving the community Nganjuk in terms of environmental control functions. Strategy Maps in the concept of Balanced Scorecard on Local Environmental Office Nganjuk as follows: a. Customer Perspectives include: Information Services water quality status, the status of ambient air quality, Public Complaints, Land Damage Due Biomass Production. b. Internal Business Process Perspective: Giving recommendation of UKL - UPL, water quality management and the establishment of classes in the spring, licensing and management location B-3 waste collection and disposal of wastewater into waterways, water quality in water resources, waste management oversight B- 3. c. Learning and Growth perspective include: Improving the skills and competence of the employees; , Increased professionalism. d. Financial perspective include: Budget Efficiency, Accountability Financial Accountability and Budget Absorption performance indicators such as level of use of budget savings, Decreased Total Audit Findings, Timeliness of Financial Statements, as well as the timeliness of budget absorption. Based on the research results can be put forward suggestions as follows suggestions: 1.Kepala Office was able to determine the problem institutions, so that decisions can be made by tepat.2. The Importance created a new organizational structure to support the implementation of strategy maps in the concept of the balanced scorecard for the achievement of agency objectives.